Peranan Ukuran Perusahaan Memoderasi Pengaruh Struktur Modal dan Total Arus Kas Terhadap Harga Saham - Ahmad Bisri; Suripto; Sugiyanto (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to provide empirical evidence of the effect of capital structure on stock prices, total cash flow on stock prices, capital structure and total cash flow on stock prices, the effect of capital structure on stock prices with company size as a moderating variable, total cash flow on stock prices with company size as a moderating variable. The population in this study are consumer goods industry sector companies listed on the IDX during 2017-2021. Determination of the sample using purposive sampling technique, obtained a sample of 14 companies with 70 observation data. Analysis techniques and hypothesis testing were carried out with panel data regression analysis through Eviews-12.0. The results revealed that the capital structure variable has no effect on stock prices, the total cash flow variable affects stock prices, the company size variable cannot moderate the effect of capital structure on stock prices, the company size variable cannot moderate the effect of total cash flow on stock prices.